Lithiophilic Silver Coating on Lithium Metal Surface for Inhibiting Lithium Dendrites - Zuo, Zefu; Zhuang, Libin; Xu, Jinzhuo; Shi, Yumeng; Su, Chenliang; Lian, Peichao; Tian, Bingbing (Frontiers in Chemistry, 2020)
Li metal batteries (LMBs) are known as the ideal energy storage candidates for the future rechargeable batteries due to the high energy density. However, uncontrolled Li dendrites growing during charge/discharge process causes extremely low coulombic efficiency and short lifespan. In this work, a thin lithiophilic layer of Ag was coated on the bare Li surface via a thermal evaporation method, which alleviated volume variations and suppressed Li dendrites growth during cycling. As a result, a long lifespan of 250 h at a current density of 1 mA cm-2 was achieved in the symmetric cell when using the Ag-modified Li foil (Ag@Li). The LiFePO4|Li full cell demonstrated an excellent cycling performance and rate capacity with a high specific capacity of 131 mAh g-1 even after 300 cycles at 0.5 C. This study offers a suitable method for stabilizing Li metal anodes in LMBs.